A New Brazilian Device for Cervical Cancer Screening: Acceptability and Accuracy of Self-sampling - Martina Lichtenfels; Noely Paula Cristina Lorenzi; Maricy Tacla; Kaori Yokochi; Flávia Frustockl; Camila Alves Silva; André Luiz da Silva; Lara Termini; Caroline Brunetto Farias (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To evaluate the accuracy and patient acceptability toward self-sampling using a new device - SelfCervix® - for detecting HPV-DNA. Methods A total of 73 women aged 25-65 who underwent regular cervical cancer screening from March to October 2016 were included. Women performed self-sampling followed by a physician-sampling, and the samples were analyzed for HPV-DNA. After that, patients were surveyed about their acceptability of self-sampling. Results HPV-DNA detection rate of self-sampling presented high accuracy and was similar to physician-collection. Sixty-four (87.7%) patients answered the acceptability survey. Most patients (89%) considered the self-sampling comfortable, and 82.5% preferred self-sampling to physician-sampling. The reasons cited were time-saving and convenience. Fifty-one (79.7%) reported that they would recommend self-sampling. Conclusion Self-sampling using the new Brazilian device SelfCervix® is not inferior in HPV-DNA detection rate compared with physician-collection, and patients are supportive of the method. Therefore, it might be an option to reach under-screened populations in Brazil.